PENGEMBANGAN PACKAGING FASHION SEBAGAI IDENTITAS VISUAL FASDEVA: STUDI PENCIPTAAN KEMASAN PRODUK FASHION BERBASIS ELEMEN MOTIF BATIK KONTEMPORER - Fadlilah Indira Sari; Silmy Ni’mah Fadhilah; Irma Russanti (BAJU: Journal of Fashion and Textile Design Unesa, 2026)
This design creation study seeks to develop fashion packaging that incorporates contemporary batik motifs as a visual identity strategy to enhance the appeal and professionalism of TEFA products. Employing a practice-led design research approach, the study comprised a sequence of activities including needs analysis, motif exploration, alternative design development, prototype production, and preference testing with a sample of 59 respondents. The results demonstrate that the integration of contemporary batik motifs across three packaging media box, totebag, and hangtag significantly reinforces brand visual identity and elevates product aesthetic value. Respondents favored the first box design (54.2%) and the first totebag design (61%), indicating a predominant preference for minimalist compositions featuring stylized batik elements. The findings further reveal that fashion packaging functions not merely as a marker of perceived product quality but also as a medium for cultural continuity through the reinterpretation of batik within a modern visual framework. This study concludes that contemporary batik-based fashion packaging effectively strengthens the visual identity of FASDEVA and enhances the marketability of TEFA fashion products. The research contributes to the discourse on culturally embedded packaging design and underscores its relevance for fashion vocational education and the broader creative industries.